Adventures Unlimited : You and Me and the Land of Lost Things - Griffiths, Andy, 1961-; Hope, Bill (New York, New York : Feiwel & Friends, 2025)
"The search for a misplaced rabbits foot leads two adventurers into encounters with a bull whos lost his temper, much missing treasure, and many, many single socks. Clad anonymously in custom-made adventure suits that cover them head to toe, the never-named narrator ("Me") and sidekick ("You") drive their supposedly "uncrashable" adventure car through an interdimensional hole into the truly crowded place where all lost things go. There they run into both a tree and treasure hunter Johnny Knucklehead. Johnny, whose head is a giant clenched fist, had been reported lost in the jungle. This meeting is just the beginning of a long series of random encounters during which even the plot is lost (and then found again), Johnny is reunited with his mirror twin, Jimmy, and a lost lucky charm is recovered--only to become a bargaining chip after the adventurers are captured by a peg-legged rabbit pirate."--Provided by publisher.
"Originally published in Australia by Pan Macmillan Australia Pty Ltd."--Title page verso.
Keywords: Multiverse -- Juvenile fiction; Multiverse -- Fiction; Adventure and adventurers -- Fiction; Action and adventure fiction; Humorous fiction